Strategy formulation for the career preparation guidance program of the EduTech Startup Brofesional.id - Hafidh Rifky Adiyatna; Fadhila Balqis (Privietlab, 2025)
This study aims to formulate development strategies and determine the priority strategies applicable to the Career Preparation Guidance Program of the edutech startup Brofesional.id. This research began by analyzing the internal and external factors influencing the program. An analysis was conducted to identify the program’s strengths, weaknesses, opportunities, and threats. To formulate strategies, this study applies the principles of strategic management and utilizes various analytical tools, including the IFE, EFE, SWOT, IE, and QSPM matrices. The findings indicate that the most feasible strategy for Brofesional.id is to enhance promotional activities through regular collaborations with government agencies. This suggested approach is supported by a QSPM analysis score of 4.807.